Muddy paws - Bentley, Sue, 1951-; Swan, Angela (New York : Grosset & Dunlap, 2008)
When Beth spends two weeks at her aunt's farm over the summer, her encounter with a magic puppy helps her make friends with her annoying cousin.
Accelerated Reader AR
Keywords: Dogs -- Fiction; Farm life -- Fiction; Cousins -- Fiction; Magic -- Fiction